2020
DOI: 10.1002/eng2.12309
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact and performance assessment of a new Zigbee‐based shotgun training system

Abstract: Only a few research works have studied the risks involving young athletes in shooting activities such as noise and risk of projectile impact. Besides, limited studies have explored the environmental concerns caused by remaining projectile fragments scattered into the environment. In recent years, there has been an increasing interest in integrating computing, modeling, and IoT‐based applications and used connected add‐ons (e.g., steams Virtual Reality VR, virtual guns, and game controllers) in sports activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Rao et al also used the Riverbed simulator to analyze the performance of different topologies of Zigbee and concluded that cluster tree performs better in scenarios where the larger network coverage is needed [37]. Few other research works on the Zigbee performance analysis are stated in [38][39][40]. The discussed research works are summarized in Table 2.…”
Section: Related Workmentioning
confidence: 99%
“…Rao et al also used the Riverbed simulator to analyze the performance of different topologies of Zigbee and concluded that cluster tree performs better in scenarios where the larger network coverage is needed [37]. Few other research works on the Zigbee performance analysis are stated in [38][39][40]. The discussed research works are summarized in Table 2.…”
Section: Related Workmentioning
confidence: 99%